THEME AND RHEME ANALYSIS AND POLITENESS STRATEGY IN DIPLOMATIC WORKPLACE WRITING: A DISCOURSE ANALYSIS - Rahardjo Rahardjo; Didin Nuruddin Hidayat; Alek Alek (Getsempena English Education Journal, 2021)
This study explores thematic progression patterns within the systemic functional linguistics (SFL) and the selection of words identified in writing within the diplomatic workplace. Politeness strategy employed between government to government communication through written diplomatic texts and its relationship with theme and rheme progression is the focus of this study. It is also aimed at raising host country EFL diplomat as well as university students’ awareness of progression patterns and the importance of persuasive writing to mitigate confrontational notions. Many researches have been conducted on public diplomacy and international relations on speeches or verbal texts but no studies on written text communication between a diplomatic office in a foreign country with the host country office announcing the arrival or departure of a diplomat from a foreign nation. To fill that gap is the reason of this study is aiming. A descriptive qualitative study was employed to analyze the theme-rheme progression patterns on a third-party-type diplomatic text of the Embassy of the United States of America addressed to the host country diplomatic consular section of the Department of Foreign Affairs of the Republic of Indonesia in Jakarta. SFL theory was applied particularly in analyzing the textual meta-function of the text to find the theme-rheme progression patterns. The result showed that the distribution of themes and rhemes in the text being analyzed follows the simple progression category.